INFLUENCE OF DIFFERENT SETT TREATMENT TECHNIQUES ON YIELD, QUALITY AND ECONOMICS OF THE SUGARCANE - A. S. PATIL,; G. R. PAWAR, (The Bioscan, 2023)
The field experiment was carried out, during 2017-18, 2018-19 and 2019-20 to evaluate the influence of different sett treatment techniques on yield, quality and economics of the sugarcane at R and D farm, Vasantdada Sugar Institute, Manjari, Pune. The treatments comprises agro chemicals viz. carbendazim 0.01%, Imidacloprid 0.003%, bio inoculant includes consortia of nitrogen fixing bacteria, as well as bio stimulants viz. Ethrel 50 ppm, oligochitosan 100 ppm were applied manually and by vacuum pressure technique (200 mm Hg for 20 min.) and sett treated with Moist Hot Air at 54°C for 150 min. Single buds setts of var. VSI 08005 were used for imposing treatments and planted in protrays. The experiment was laid out in completely randomized block design with three replications. Based on results of the experiment significantly higher cane yield (171.17 t/ha), sett yield (8.66 lakh/ha two budded setts) and Benefit:Cost ratio (1:2.77 by cane yield and 1:6.44 by sett yield) was obtained in sett treated with Moist Hot Air at 54°C for 150 min. Sett treated with Ethrel (50 ppm) manually and by vacuum pressure technique showed superior germination.